KEPEMIMPINAN PEREMPUAN DALAM PANDANGAN ISLAM - Zaini, Ahmad; Umam, Ahmad Hadiqul; Sodik, Al Muzafar; Kirom, Muhammad Agorrul (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
Women taking on leading roles is a common occurrence in many parts of the world today. So, we need to know the rules of a group or organization led by a woman, as well as the rules of a very big country. This paper mostly talks about three things. The first is about the verses in the Qur'an and the sayings of the Prophet that, when looked at lafadz, show that women can't be in charge. This will be described in more detail. In the second discussion, a verse is given that scholars use to say that a woman can lead a group, organization, or state. This is followed by the scholars' interpretations of these verses, which can be used as evidence that a woman can be a leader. Then, in the last discussion, stories were told about women in charge, because this isn't a new thing. It's been happening since ancient times, which makes us sure and think that a woman can be in charge of an organization.